GKT137831 and hydrogen peroxide increase the release of 6-nitrodopamine from the human umbilical artery, rat-isolated right atrium, and rat-isolated vas deferens - Britto-Júnior, José; Furlaneto, Rafael; Lima, Antonio Tiago; de Oliveira, Mariana Gonçalves; Severino, Beatrice; Frecentese, Francesco; Fiorino, Ferdinando; Caliendo, Giuseppe; Muscará, Marcelo Nicolás; De Nucci, Gilberto (Frontiers in Pharmacology, 2024)
Introduction: The human umbilical artery (HUA), rat-isolated right atrium, and rat-isolated vas deferens present a basal release of 6-nitrodopamine (6-ND). The basal release of 6-ND from these tissues was significantly decreased (but not abolished) when the tissues were pre-incubated with Nω-nitro-L-arginine methyl ester (L-NAME). Methods: In this study, the effect of the pharmacological modulation of the redox environment on the basal release of 6-ND was investigated. The basal release of 6-ND was measured using Liquid chromatography with tandem mass spectrometry (LC-MS/MS). Results and Discussion: Pre-incubation (30 min) of the tissues with GKT137831 (1 μM) caused a significant increase in the basal release of 6-ND from all tissues. In the HUA, pre-incubation with diphenyleneiodonium (DPI) (100 μM) also caused significant increases in the basal release of 6-ND. Preincubation of the HUA with hydrogen peroxide (H2O2) (100 μM) increased 6-ND basal release, whereas pre-incubation with catalase (1,000 U/mL) significantly decreased it. Pre-incubation of the HUA with superoxide dismutase (SOD) (250 U/mL; 30 min) also significantly increased the basal release of 6-ND. Preincubation of the HUA with either allopurinol (100 μM) or uric acid (1 mM) had no effect on the basal release of 6-ND. Pre-treatment of the HUA with L-NAME (100 μM) prevented the increase in the basal release of 6-ND induced by GKT137831, diphenyleneiodonium, and H2O2. The results obtained indicate a major role of endogenous H2O2 and peroxidases as modulators of 6- ND biosynthesis/release and a lack of peroxynitrite contribution.